(untitled) (Revista de Ciências Agroveterinárias, 2011)
The common bean root rots caused by pathogenic fungi inhabitants of soil, present variation in intensity in different products regions of Brazil. The objective of this study was to determine the incidence of root rot in adult plants and the grain yield reduces in black beans cultivars BRS Campeiro, BRS Valente and IPR Uirapuru. The experiments were performed in the agricultural harvests 2004/05, 2005/06 and 2006/07, in county of Muitos Capões, RS, in no-tillage area under the crop rotation with corn in the summer and in succession with wheat in the winter. In harvest, ten linear meters of plants were uprooted, on five points randomized in the crop, determining the total number of plants and the number of diseases plants. The grain yield damage was obtained by difference between the estimate of real yield and potential yield. The identification of predominant fungi in diseases plants was based on symptoms and fragments isolation of root in Potato-Dextrose-Agar medium. The average incidence of root rot were 24.5%, 40.6% and 22%, with 2.8%, 4.1% and 2.4% average damage in grain yield, respectively, for 2004/05, 2005/06 and 2006/ 07, not differ significantly. There was no significant correlation between the incidence and damage when compare the cultivars within the agricultural season and also for medium of cultivars between seasons. The fungus Macrophomina phaseolina presented more frequently in 2004/05 and 2005/06, and Fusarium spp. was more frequent in 2006/07. The inconsistency of the fungi frequency identified in the cultivars and in the three agricultural seasons do not permission identify the relationship between genotype and susceptibility to pathogen.